1981
DOI: 10.1152/ajpheart.1981.241.2.h268
|View full text |Cite
|
Sign up to set email alerts
|

Continuous blood pressure measurement in rats with aortic baroreceptor deafferentation

Abstract: The purpose of this study was to determine if once-daily arterial pressure measurements are a reliable estimate of actual time-averaged arterial pressure in neurogenic hypertensive rats. Male rats were subjected to either aortic baroreceptor deafferentation (ABD, n = 10) or sham operation (SO, n = 10). One to 3 mo later, arterial pressure (AP) was recorded from a chronic indwelling catheter in each rat for 72 continuous hours. Subsequently, AP was determined once a day (10- to 30-min recording periods) in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
9
0
2
Order By: Relevance
“…Comparable results were obtained from 1-hour and 24-hour recordings regardless of whether the mean or median value of each MAP frequency distribution was used (see Table 1). Thus, our results agree with those of Fink et al , 31 who found that brief daily recordings of intra-arterial pressure produced an average MAP that was the same as that calculated from continuous 24-hour recordings. However, their measurement procedure precluded assessment of the variability of the MAP during short-term recording sessions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Comparable results were obtained from 1-hour and 24-hour recordings regardless of whether the mean or median value of each MAP frequency distribution was used (see Table 1). Thus, our results agree with those of Fink et al , 31 who found that brief daily recordings of intra-arterial pressure produced an average MAP that was the same as that calculated from continuous 24-hour recordings. However, their measurement procedure precluded assessment of the variability of the MAP during short-term recording sessions.…”
Section: Discussionsupporting
confidence: 93%
“…However, we noted that depressor responses were frequently associated with changes in body position or locomotion in SAD rats, an observation made in several other studies. 31 ' 4041 In contrast, the direction of change in the MAP of NTS lesion rats was not necessarily related to such behavior. Sinoaortic-denervated rats have been shown to exhibit augmented vasodepressor responses to centrally applied catecholamines.…”
mentioning
confidence: 95%
“…The lowest stable MAP recorded continuously for Ն10 minutes was taken as the value for the recording session. 13 …”
Section: Hemodynamic Measurementsmentioning
confidence: 99%
“…The remaining 50% could be considered to have a partial SAD, with their TGSI ranging from 8.09 to 8.24. On the other hand, several early studies (32)(33)(34)(35) focused on the cardiovascular and neural effects of AD (a form of partial barodenervation) in rats. However, the lack of any individual test for the extent of barodenervation makes it difficult to derive valid conclusions from these studies.…”
Section: Discussionmentioning
confidence: 99%